2021
DOI: 10.15700/saje.v41n3a1849
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of English as a first additional language: Fourth grade reading teachers’ perspectives

Abstract: The study reported on here was designed to investigate the challenges faced by teachers when teaching reading in Grade 4 English First Additional Language (EFAL) in East London, South Africa. This research study was framed by the socio-constructivist theory of reading. A case study design that corresponds with the constructivist paradigm was used to gather qualitative data. Semi-structured interviews and observations were conducted with 12 teachers who were purposively selected from 4 public schools (2 English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This highlights the fact that many learners (76%) are learning in their second language and are not performing to the same level as those who speak the same language at home. The low literacy rate has been attributed to the transition from mother tongue (Grades R-3) to English as a language of learning and teaching (LOLT) from Grade 4 onwards (Fesi & Mncube 2021).…”
Section: Reading Comprehension Skills and The English As A Second Lan...mentioning
confidence: 99%
See 4 more Smart Citations
“…This highlights the fact that many learners (76%) are learning in their second language and are not performing to the same level as those who speak the same language at home. The low literacy rate has been attributed to the transition from mother tongue (Grades R-3) to English as a language of learning and teaching (LOLT) from Grade 4 onwards (Fesi & Mncube 2021).…”
Section: Reading Comprehension Skills and The English As A Second Lan...mentioning
confidence: 99%
“…The majority of learners prefer English as a language of teaching and learning and communication because of its status internationally. Fesi and Mncube (2021) pointed out that many people view proficiency in English as equal to access to employment, higher education and a better life. Similarly, Bukhari (2022) revealed that students preferred English as a medium of instruction as they believe it maximises students' future and international opportunities.…”
Section: Reading Comprehension Skills and The English As A Second Lan...mentioning
confidence: 99%
See 3 more Smart Citations